The Holy Quran : a historical survey of calligraphy in the Quran. (MasterVision humanities series. Religion, 1980)
The holy Quran describes preservation of the sacred text through the oral tradition of recitation and the written tradition of calligraphy. Islam and the sciences describes the accomplishments of Arabic scientists and mathematicians and relates this search for knowledge to the Islamic concept of unity. The religious experience explores religion as a manifestitation of man's search for meaning.